ANALISIS PELUANG PENGHEMATAN ENERGI KOMPRESOR DAN PENURUNAN EMISI: Studi Kasus di PT. MEI - Hendri Hendri (Universitas Mercu Buana, 2018)
The current energy supply crisis is a strategic issue and therefore needs to be analyzed for Energy saving opportunities. Thermal Power Station with a capacity of 2 units x 60 MW at PT.MEI uses Compressor to operate its production. The method of analysis of energy saving compressor opportunity is by observation method, measurement, data and analysis using software tools which released by SEAI (Sustainability Energy Authority of Ireland). Result of research, it is known that the opportunity to save electricity energy is 703.644 kWh/year or Rp 422.186.296/ year and the decrease of emission of 579 CO2 (Ton).